Transforming growth factor-beta 1 is a negative modulator of adult neurogenesis - Winner, Beate; Couillard-Despres, Sebastien; Winkler, Jürgen; Bogdahn, Ulrich; et al. (Journal of Neuropathology and Experimental Neurology, 2006)
Transforming growth factor (TGF)-beta 1 has multiple functions in the adult central nervous system (CNS). It modulates inflammatory responses in the CNS and controls proliferation of microglia and astrocytes. In the diseased brain, TGF-beta 1 expression is upregulated and, depending on the cellular context, its activity can be beneficial or detrimental regarding regeneration. We focus on the role of TGF-beta 1 in adult neural stem cell biology and neurogenesis. In adult neural stem and progenitor cell cultures and after intracerebroventricular infusion, TGF-beta 1 induced a long-lasting inhibition of neural stem and progenitor cell proliferation and a reduction in neurogenesis. In vitro, although TGF-beta 1 specifically arrested neural stem and progenitor cells in the G0/1 phase of the cell cycle, it did not affect the self-renewal capacity and the differentiation fate of these cells. Also, in vivo, TGF-beta 1 did not influence the differentiation fate of newly generated cells as shown by bromo-deoxyuridine incorporation experiments. Based on these data, we suggest that TGF-beta 1 is an important signaling molecule involved in the control of neural stem and progenitor cell proliferation in the CNS. This might have potential implications for neurogenesis in a variety of TGF-beta 1-associated CNS diseases and pathologic conditions.
Keywords: brain repair; cell fate; differentiation; doublecortin; neurodegenerative diseases